Sequence-specific RNA cleavage by PNA conjugates of the metal-free artificial ribonuclease tris(2-aminobenzimidazole) - Danneberg, Friederike; Ghidini, Alice; Dogandzhiyski, Plamena; Kalden, Elisabeth; Strömberg, Roger; Göbel, Michael W. (Beilstein Journal of Organic Chemistry, 2015)
Tris(2-aminobenzimidazole) conjugates with antisense oligonucleotides are effective site-specific RNA cleavers. Their mechanism of action is independent of metal ions. Here we investigate conjugates with peptide nucleic acids (PNA). RNA degradation occurs with similar rates and substrate specificities as in experiments with DNA conjugates we performed earlier. Although aggregation phenomena are observed in some cases, proper substrate recognition is not compromised. While our previous synthesis of 2-aminobenzimidazoles required an HgO induced cyclization step, a mercury free variant is described herein.
Keywords: antisense; fluorescence correlation spectroscopy; guanidine; miRNA 20a; peptide nucleic acids